(untitled) - Gylfason, Thorvaldur; Thorvaldur Gylfason (Oxford [u.a.], 1999)
This is a concise and reader-friendly introduction to the principles of economic growth for students of economics and business. Thorvaldur Gylfason examines theoretical and empirical models of economic growth through case studies drawn from around the world and gives a trenchant analysis of classic thought in this area. The influence of public policy on economic efficiency and growth is a key theme
Keywords: Economic development; Economic history